The role of CAP3 in CD95 signaling: new insights into the mechanism of procaspase-8 activation - Golks, Alexander; Krammer, Peter H.; Lavrik, Inna N. (Cell death and differentiation, 2006)
Formation of the CD95 (APO-1/Fas) death inducing signaling complex (DISC) plays a central role in CD95 signaling. Previously, CD95 DISC composition was analyzed by two-dimensional gel electrophoresis and four major cytotoxicity-associated proteins (CAP1-4) were found. CAP1 and CAP2 were defined to be unmodified and phosphorylated FADD, respectively. CAP4 was identified as procaspase-8a. CAP3, however, has remained elusive. In this study, we demonstrate that CAP3 is an intermediate of procaspase-8 processing. CAP3 is generated within seconds of DISC formation and subsequently processed to the prodomain of procaspase-8a that is known as p26 (CAP5). These findings lead to new insights into the mechanism of procaspase-8 processing and apoptosis initiation.
Published: 23 September 2005
Gesehen am 04.03.2021